Clinical features of posterior microphthalmos associated with papillomacular fold and high hyperopia. (10th May 2016) - Park, Shin Hae; Ahn, Ye Jin; Shin, Sun Young; Lee, Young Chun
Abstract : Background: The aim was to evaluate the characteristic clinical features of posterior microphthalmos. Methods: Medical records of four patients (eight eyes) between the ages of three and 31 years with posterior microphthalmos were reviewed retrospectively. Thorough ocular examinations were performed, including visual acuity, intraocular pressure, ocular alignment, axial length, cycloplegic refraction, slitlamp biomicroscopy of the anterior segment and fundus and spectral‐domain optical coherent tomography (SD‐OCT). Results: All subjects had presented with high hyperopia (+11.0 to +15.75 D) and retinal papillomacular folds in both eyes. They also had reduced bilateral axial length (15.55–18.61 mm), with foreshortening of the posterior segment and a relatively normal anterior segment. Papillomacular retinal folds involving the inner retinal layers and sparing the outer retinal layers, along with the absence of foveal depression, were confirmed by macular SD‐OCT. In three patients, we found esodeviations associated with posterior microphthalmos and one of these required strabismic surgery. Concomitant optic nerve hypoplasia and a newly‐developed neurosensory retinal detachment were found in one patient. Conclusion: Posterior microphthalmos is a developmental arrest of ocular growth. In addition to high hyperopia and retinal papillomacular folds, various types of esotropia, optic disc hypoplasia and neurosensory retinal detachment may accompany posterior microphthalmos. In particular, children with posterior microphthalmos require early appropriate management of the high refractive error and resultant esotropia.